Barriers to adherence in time-restricted eating clinical trials: An early preliminary review - O'Neal, Monica A.; Gutierrez, Nikko Rigor; Laing, Kyla L.; Manoogian, Emily N. C.; Panda, Satchidananda (Frontiers in Nutrition, 2023)
Time-restricted eating (TRE) has shown potential benefits in optimizing the body’s circadian rhythms and improving cardiometabolic health. However, as with all dietary interventions, a participant’s ability to adhere to the protocol may be largely influenced by a variety of lifestyle factors. In TRE trials that reported participants’ rates of adherence, the percentage of total days with successful adherence to TRE ranged from 47% to 95%. The purpose of this review is to 1) summarize findings of lifestyle factors affecting adherence to TRE among community-dwelling individuals, and 2) explore a recommended set of behavioral intervention strategies for the application of TRE. A literature search on Pubmed was conducted to identify clinical TRE studies from 1988 to October 5, 2022, that investigated TRE as a dietary intervention. 10 studies mentioned a combination of family, social, work, and miscellaneous barriers. To maximize participant adherence to TRE and increase the reliability of TRE clinical trials, future studies need to address these barriers to TRE adherence.